Murine intracisternal type A particles: a biochemical characterization. - Wong-Staal, F (1975)
Intracisternal A particle preparations from a murine neuroblastoma cell line (N18) and from a mineral oil-induced murine plasmacytoma (MOPC-104E) contain both an endogenous RNA-dependent DNA polymerase activity and high molecular-weight polyadenylic acid (poly[A])-containing RNA. The DNA polymerase activity is stimulated by oligo(dG)-poly(C) and oligo(dT)-poly(A) and to a lesser extent by oligo(dT)-poly(dA), in agreement with previous reports. The high-molecular-weight RNA is predominantly 35S and contains a poly(A) tract of approximately 220 nucleotides as judged by polyacrylamide gel electrophoresis. Small amounts of 70S RNA are also present. This RNA preparation contains RNA homologous to RNA from type-C particles, as judged by molecular hybridization experiments. However, since this RNA derives only in part from A-particles and in part from other cellular RNA, hybridization of A-particle endogenously synthesized DNA or reverse transcripts of A-particle RNA to purified type C viral 70S RNA may more accurately reflect the relationship of A-particle RNA to RNA from C-particles. None of these DNA transcripts hybridizes significantly to C-particle 70S RNA, although MOPC and N18 DNA transcripts share significant homology. Our interpretation of these results is that murine intracisternal A particles are not closely related genetically to the tested murine type C viruses, although an alternate possibility is that all the A-particle DNA transcripts are copied from only a small part of the genome, which is unrelated to C-particle RNA.